The Impact of Fiscal Decentralization on Human Development Outcomes and Income Equality at the Provincial Level in Indonesia - Wiwiek Rindayati; Lailatun Nikmah; Gerhana Gerhana; Zhena Nofhatiaz Zahra (Institute of Multidisciplinary Research and Community Service, 2026)
Fiscal decentralization since the reform era has transformed regional development policies in Indonesia. However, its effectiveness in enhancing human development and reducing income inequality varies across regions and across the empirical literature. This study analyzes the impact of fiscal decentralization reflected through the degree of fiscal decentralization, education expenditure, and health expenditure on the Human Development Index and Gini coefficient, with poverty rate, GDP per capita, and open unemployment rate as control variables. Panel data from 34 Indonesian provinces for the period 2017-2023 were used. This study employed two types of analysis: qualitative and quantitative. Qualitative analysis was used to describe the state of fiscal decentralization, the Human Development Index, and income inequality across Indonesia’s 34 provinces from 2017 to 2023. A typological classification was then conducted to map regional conditions across four quadrants. Quantitative analysis was used to examine the impact of fiscal decentralization on the Human Development Index and income inequality at the provincial level in Indonesia. The analytical technique employed was panel data regression, combining cross-sectional and time-series data. The time-series data used covers the years 2017 to 2023, while the cross-sectional data consists of data from 34 provinces in Indonesia. Data processing was performed using Microsoft Office Excel 2021 and EViews 10. The findings indicate that fiscal decentralization has a significant positive effect on HDI (0.14) and a significant negative effect on inequality (-0.00). The research findings imply the need to enhance regional fiscal autonomy, prioritize education and health budget allocation, and optimize regional development. Keywords: Fiscal decentralization; Human development; Income inequality; Panel data